2007
DOI: 10.1177/030089160709300306
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection for Hepatocellular Carcinoma: a Multivariate Analysis of Factors Associated with Improved Prognosis. the Role of Clinical, Pathological and Surgical Related Factors

Abstract: The treatment of hepatocellular carcinoma should be both the most radical to obtain the best outcome and to reduce the recurrence's rate, and the most suitable according to the patient's condition, lesion's characteristics and underlying liver disease: because of the large number of factors affecting the outcome of Hcc, unfortunately, we are still far from an agreement upon a group of criteria useful to select the best candidates for liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…Hepatic resection for HCC is now considered a safe operation with a low surgical morbidity rate. The present study has shown improved survival after curative primary resection for HCC over a 15-year interval with the advancement of surgical techniques and postoperative care 5 . However, postoperative complications were independently associated with worse overall survival.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Hepatic resection for HCC is now considered a safe operation with a low surgical morbidity rate. The present study has shown improved survival after curative primary resection for HCC over a 15-year interval with the advancement of surgical techniques and postoperative care 5 . However, postoperative complications were independently associated with worse overall survival.…”
Section: Discussionmentioning
confidence: 51%
“…The hepatic resection techniques used have been described previously 5 . Briefly, the operation started with a bilateral subcostal incision or right subcostal incision with upward midline extension.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively speaking, all the evaluated staging systems employed similar clinical and pathological variables that were previously shown to be prognostic in HCC, such as tumor size, tumor number, and vascular invasion [27][28][29]. This might, at least to some intent, ensure the applicability of them in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these studies retrospectively analyzed patients with liver resection for hcc to glean information on the prognostic values of clinical, surgical, pathologic, and biologic factors affecting long-term outcome and intrahepatic recurrence [26][27][28][29][30][31] . For example, in a retrospective analysis, Ramacciato et al reported that viral cause of cirrhosis, presence of multiple nodules, and vascular invasion negatively affected recurrence rate and long-term survival 30 .…”
Section: Role Of Resection In Hccmentioning
confidence: 99%